2012
DOI: 10.1007/s00277-012-1575-2
|View full text |Cite
|
Sign up to set email alerts
|

Repression of STAT3, STAT5A, and STAT5B expressions in chronic myelogenous leukemia cell line K–562 with unmodified or chemically modified siRNAs and induction of apoptosis

Abstract: Signal transducers and activators of transcription (STAT) proteins are latent cytoplasmic transcription factors that affect several cellular processes including cell growth, proliferation, differentiation, and survival. Following phosphorylation, STATs are activated, and their upregulated expressions increase in malignancies with playing a role in the development of leukemia. In this study, transfection of K-562 cells with either unmodified or chemically modified anti-STAT3, -STAT5A, -STAT5B siRNAs for duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
1
9
0
3
Order By: Relevance
“…Besides STAT5A, also STAT3 has significant roles in hematological malignancies as we and others also have reported before [22,23]. Similar to our inferences about the significance of JAK/STAT pathway members-especially STAT family, Rozovski U et al reported that STAT3 regulated microRNA gene expression in chronic lymphocytic leukemia cells and presence of activated STAT3 had a profound effect on miRNA expression in CLL cells [24].…”
Section: Discussionsupporting
confidence: 89%
“…Besides STAT5A, also STAT3 has significant roles in hematological malignancies as we and others also have reported before [22,23]. Similar to our inferences about the significance of JAK/STAT pathway members-especially STAT family, Rozovski U et al reported that STAT3 regulated microRNA gene expression in chronic lymphocytic leukemia cells and presence of activated STAT3 had a profound effect on miRNA expression in CLL cells [24].…”
Section: Discussionsupporting
confidence: 89%
“…However, data regarding siRNA targeted silencing of STAT genes for cancer therapy are limited to in vitro studies and in vivo studies of animal models only [72-81]. …”
Section: Introductionmentioning
confidence: 99%
“…Kapsaisinin CCRF-CEM hücreleri için belirlenmiş IC 50 dozu olan 80 μM ile deney setleri oluşturuldu 16 . İnkübasyonundan 72 saat sonra apoptoz analizi ve mRNA seviyesindeki gen ekspresyon analizi için sırasıyla 5x10 6 ve 1x10 6 hücre toplandı.…”
Section: Kapsaisin Muamelesiunclassified
“…Sonuçlarımıza benzer olarak Zhang ve arkadaş-ları da 3 adet T hücreli lösemi hücre dizisine kapsaisin verdikten sonra, lösemi hücrelerinin proliferasyonunun inhibe edildiğini, apoptozun indüklendiğini rapor etmişlerdir. Ayrıca, 100 ve 200 μM kapsaisin 24 saat süreyle uygulandığında, CTL-1 hücre dizisinde sırasıyla %5,4 ve % 32,2 oranlarında apoptoz artışı saptanmışken, ATL-T hücrelerinde aynı dozlar için sırasıyla %8,8 ve %19,8 oranlarında artmış apoptoz gözlenmiştir 16 . Ito ve arkadaşlarının insan akut myeloid lösemi hücre dizileri NB4 ve Kasumi-1'e kapsaisin verdikleri çalışmalarında, G 0 /G 1 fazında hücre döngüsünü durdurması ve apoptozu indüklemesi suretiyle lösemi hücrelerinin proliferasyonu baskılanır-ken; normal kemik iliği mononükleer hücrelerin etkilenmediği görülmüştür 18 .…”
Section: Tartıșmaunclassified